Letter (copy) : Gunnar Ebb - Citrine, Walter, 1887-1983
013-0096-001 Secretary's. WMC/FEM/KMS/608. 18th March, 1940. Mr. Alan. W. Gilchrist, International Brigade Association, 115, Shaftesbury Avenue, London. W.C.2. Dear Sir, re GUNNAR EBB I am in receipt of your letter of March 15th with regard to Gunnar Ebb. As you state that this man is a refugee from Finland it makes me wonder whether the fact you mention was the only charge against him. Others who equally fought the Government during the period of the Civil War and who were no doubt equally good Socialists and Democrats, have now been fighting with the Finnish Government against Russia. Yours faithfully, General Secretary. 292/946/13/96